Epidemiology of Osteoarthritis: Literature Update - Vina, Ernest R. (Curr Opin Rheumatol, 2018)
PURPOSE OF REVIEW: The purpose of this review is to highlight recent studies of osteoarthritis epidemiology, including research on prevalence, disease impact, and potential risk factors. RECENT FINDINGS: Osteoarthritis (OA) is highly prevalent in the US and around the globe. It is a leading cause of disability and can negatively impact people’s physical and mental well-being. Healthcare resources and costs associated with managing the disease can be substantial. There is increasing evidence that there are different OA phenotypes that reflect different mechanisms of the disease. Various person-level risk factors are recognized, including sociodemographic characteristics (e.g., female gender, African-American race), genetic predispositions, obesity, diet-related factors, and high bone density/mass. Joint-level risk factors include specific bone/joint shapes, thigh flexor muscle weakness, joint malalignment, participation in certain occupational/sports activities, and joint injury. Recent studies have enhanced our understanding of pre-radiographic lesions associated with OA. SUMMARY: Application of these new findings may allow us to develop innovative strategies and novel therapies with the purpose of preventing new disease onset and minimizing disease progression.